Service Quality of Tomohon Municipal Market Agency at Tomohon Beriman Market - Ruddie Albert Lengkong; Wilson Bogar; Recky Sendow (Asia Pacific Journal of Management and Education (APJME), 2021)
This study aims to analyze and explain the quality of public services at Tomohon Municipal Market Agency. The research method used a qualitative approach and informants as data sources were determined by purposive (purposive sampling) and snowball sampling. Data was collected through interview, observation, and documents. Data analysis is an interactive qualitative analysis with data analysis activities, which are data reduction, data presentation, and drawing conclusions or verification. The results showed that the public service quality of Tomohon Municipal Market Agency responded by the community as service recipients, traders or sellers and visitors of Tomohon Beriman Market was not satisfactory. This response is based on an assessment of 4 out of the 5 dimensions used to analyze and measure service quality, (1) physical aspects (tangibles), (2) dimensions of awareness or desire to help the community or customers and provide fast service, (3) dimensions of politeness, trust, and respect for consumers, and (4) dimensions of approaching, and trying to determine consumers’ wants and needs have not been implemented properly, excluding for dimension (5) the ability to provide services appropriately and correctly has shown the professionalism expected in carrying out its services.